Brief Report: Serpin Spi2A as a Novel Modulator of Hematopoietic Progenitor Cell Formation. (September 2014) - Li, Lei; Byrne, Susan M.; Rainville, Nicole; Su, Su; Jachimowicz, Edward; Aucher, Anne; Davis, Daniel M.; Ashton‐Rickardt, Philip G.; Wojchowski, Don M.
Abstract Prime regulation over hematopoietic progenitor cell (HPC) production is exerted by hematopoietins (HPs) and their Janus kinase‐coupled receptors (HP‐Rs). For HP/HP‐R studies, one central challenge in determining specific effects involves the delineation of nonredundant signal transduction factors and their lineage restricted actions. Via loss‐of‐function studies, we define roles for an HP‐regulated Serpina3g/Spi2A intracellular serpin during granulomyelocytic, B‐cell, and hematopoietic stem cell (HSC) formation. In granulomyelocytic progenitors, granulocyte macrophage colony stimulating factor (GMCSF) strongly induced Serpina3g expression with Stat5 dependency. Spi2A‐knockout (KO) led to 20‐fold decreased CFU‐GM formation, limited GMCSF‐dependent granulocyte formation, and compromised neutrophil survival upon tumor necrosis factor alpha (TNF‐α) exposure. In B‐cell progenitors, Serpina3g was an interleukin‐7 (IL7) target. Spi2A‐KO elevated CFU‐preB greater than sixfold and altered B‐cell formation in competitive bone marrow transplant (BMT), and CpG challenge experiments. In HSCs, Serpina3g/Spi2A expression was also elevated. Spi2A‐KO compromised LT‐HSC proliferation (as well as lineageneg Sca1pos Kitpos (LSK) cell lysosomal integrity), and skewed LSK recovery post 5‐FU. Spi2A therefore functions to modulate HP‐regulated immune cell and HSC formation post‐5‐FU challenge. Stem Cells2014;32:2550–2556